Ornithobacterium hominis isolates from a South African birth cohort - De Allende, Celine (Department of Molecular and Cell Biology, 2025)
Ornithobacterium hominis is a gram-negative bacterium that colonises the infant nasopharynx. Ornithobacterium hominis 16S rRNA gene sequences have been identified in South-East Asia, Australia, Gambia and Kenya; however, this species is notably absent from cohorts based in the northern hemisphere. Recent microbiome data from the Drakenstein Child Health Study (DCHS) has shown that O. hominis is present in South Africa; however, there is a lack of microbiological data regarding this species in Africa. Only a few strains have been isolated since its discovery, all of which are from Australian samples, and most data available for this species is generated from metagenomic data and short-read assemblies. Ornithobacterium hominis has been shown to colonizes the nasopharynx at high proportional abundances, especially in settings with disproportionately high pneumonia burden. However, due to the limited data, the implications of this species on disease progression are unclear; furthermore, genomic data and longitudinal carriage data suggest that O. hominis could impact the microbiome of the nasopharynx, possibly influencing disease progression. We describe the carriage and evolutionary dynamics of O. hominis in a South African birth cohort by screening available 16S rRNA data and employing standard microbiological and whole genome sequencing techniques. Methods: Available 16S rRNA sequencing data from the DCHS was screened for O. hominis sequences. Candidate samples were selected for microbiological isolation of O. hominis. Ornithobacterium hominis was isolated on Columbia blood agar in a humid, high CO2, microaerophilic incubator and identity was confirmed using a combination of standard PCR, 16S gene end-sequencing, and Gram staining. Colony morphologies and Gram-stain characteristics of the South African O. hominis isolates were determined and antibiotic susceptibility determined. For whole genome sequencing, DNA was extracted, assessed for quality, and sequenced using the Oxford Nanopore technologies platform. Genomes were assembled using an in-house bioinformatic pipeline. Genomes were analysed and compared using standard bioinformatic tools and a core genome pangenome analysis was performed. Results: Ornithobacterium hominis was present in 32% of samples and abundance increased after six months of age in the cohort. Ornithobacterium hominis was isolated and characterised. The species exhibited four main colony morphologies: punctiform, uniformly sized, mixed and mucoid. Antibiotic susceptibility testing demonstrated that all isolates were susceptible to β-lactam antibiotics and resistant to polymyxin B. Six O. hominis genomes were assembled into 2 Mb-sized circular contigs and annotated. Virulence factors such as vapD, antimicrobial resistance genes such as cfxa, including several adhesins, and a putative plasmid were identified. In addition, three distinct lipopolysaccharide biosynthesis clusters were identified, and the rearrangement hotspot cluster structure was resolved. South African O. hominis strains were found to be more closely related to Australian strains than to Maela strains from Thailand. Finally, core genes were assigned functions and categorised. Conclusion: We report some of the first O. hominis isolates and genomes assembled from cultured isolates in Africa. More strains will have to be isolated to gain a better understanding of species diversity. It is essential to investigate the interactions of this species with other respiratory tract organisms to obtain better insights into its function/role in nasopharyngeal microbiome and how it may influence disease risk. Further characterisation of the species, especially in sub-Saharan Africa, is warranted.